Zdravljenje prekanceroz materničnega vratu - Lomšek, Mili (Zdravniški vestnik, 2003)
Background. Successful diagnosis and management of cervical intraepithelial neoplasia (CIN) prevent the occurrence of invasive cervical cancer, which is one of the important indicators of the national health care. Methods. The retrospective analysis studies patients at Department of Obstetrics and Gynecology, University Medical Centre Ljubljana, who had in the period from January 1990 to December 2000 cervical biopsy due to CIN suspicion, based on abnormal PAP smear test and/or abnormal colposcopy. The patients, whose CIN diagnosis was confirmed with cervical biopsy sample histology, were treated bylocal methods (laser vaporisation, laser conization, large loop excision of the transformation zone (LLETZ), cold-knife conization), hysterectomy or just supervised with 4-6 month PAP smear and colposcopy follow-up. Our efficiency criteria were PAP smear one year after the treatment and excised tissue histology (for local excision methods and hysterectomy). We also compared the histology of the cervical biopsy sample and the excised tissue after excision methods of treatment and hysterectomy. The sources of our database were the patients' records. Results. The study analyses 800 patients. In 195 women (24%) CIN wasn't confirmed by cervical biopsy sample histology. In the remaining 605 patients (76%), we diagnosed evere dysplasia (CIN III) in 332 women (55%), moderate dysplasia (CIN II) in 153 women (25%) and light dysplasia (CIN I) in 120 women (20%). CIN was most frequently diagnosed in theage between 30 and 34. CIN III was most frequently treated with cold-knife conization and CIN II with laser vaporisation. We also treated 120 patients (66%) with CIN I, mostly with laser vaporisation. There were no substantive differences in therapeutic efficacy between the methods of treatment. (Abstract truncated at 2000 characters).
Keywords: Cervical Intraepithelial Neoplasia; Conization; ginekologija; Histerektomija; Hysterectomy; Konizacija; Laser Coagulation; Laserska koagulacija; Maternica, vrat, intraepitelijska neoplazija; maternični vrat; metode; prekanzeroze; Surgery; therapy; Vaginal Smears; Vaginalni razmazi; zdravljenje